Effects of dust, formaldehyde and delayed feeding on early postnatal development of broiler chickens. (June 2017) - de Gouw, Pieter; van de Ven, Lotte J.F.; Lourens, Sander; Kemp, Bas; van den Brand, Henry
Abstract: We investigated effects of perinatal exposure to dust or formaldehyde and the moment of first feed intake after hatching on broiler chicken development during the first week of life. Four environmental treatments were used from 468 until 512 h of incubation: control (CONT), heat treated dust (HTD), untreated dust (UTD) or formaldehyde disinfection (FORM). After hatching, all chickens were assigned to 1 of 2 feeding treatments: early feeding (EF; feed and water available in the hatcher) or delayed feeding (DF). After 512 h of incubation (day 0), chickens were reared until day 7 of age. In DF chickens, body weight (BW), yolk free body mass (YFBM) and relative liver weight did not differ among environmental treatments at day 0. However, in EF chickens BW at day 0 was greater in HTD chickens than in UTD and FORM chickens. YFBM in EF chickens at day 0 was greater when chickens were exposed to HTD compared to the other environmental treatments. In EF chickens, relative liver weight was greater in HTD chickens than in FORM. In DF chickens, BW at day 0 was positively related with hatching time (HT). In EF chickens, YFBM was positively related to HT. Residual yolk weight at day 0 was positively related with HT, whereas relative liver weight and microbicidal capacity were negatively related with HT. This study demonstrated that formaldehyde and dust during the hatching phase affect broiler chicken development at pulling from the incubator, but not at day 7. Highlights: Chickens were exposed to dust or formaldehyde during the perinatal period. Half of the chickens were provided with feed and water immediately after hatching. In early fed chickens, dust increased body weight and yolk free body weight. Later hatching chickens were further developed. Later hatching chickens had lower microbicidal capacity.